Pengaruh Investasi Terhadap Pengentasan Kemiskinan Melalui Mediasi Pertumbuhan Ekonomi Provinsi Bali - Arshanti, Kadek Novita; Wirathi, I Gusti Ayu Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
Poverty and economic growth is an important indicator to see the success of a country's development and economic growth are well demonstrated by the high level of investment in an area. Province of Bali is one of the areas that have high levels of economic growth and rapid investment, but amid the rapid development of the economy that occurred, the number of poor people is still very high. The purpose of this study to determine how the direct influence of economic growth, investment and poverty as well as the effect of indirect investment through economic growth on poverty in the province of Bali. This study uses secondary data analysis method path (Path Analysis), to determine the direct relationship of independent variables on the dependent variable and the relationship indirectly through intervening variables. The results showed that direct investment variables significant negative effect on poverty, direct investment variable positive significant effect on economic growth, variables directly affect economic growth negative significant impact on poverty and the effect of the investment on poverty through economic growth that is equal.   Keywords : Investment , Poverty , Economic Growth